Organizational Citizenship Behavior and Psychological Capital in Pre-Kindergarten Teacher’s Well-Being - Sufya, Dina Haya; Lina Eka Retnaningsih (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The characteristics of Organizational Citizenship Behavior (OCB) include empathy, conscientiousness, civic participation, and politeness. On the other hand, psychological capital turns on self-efficacy, hope, resilience, and optimism. The design of this study is quantitative using variance-based Structural Equation Model (SEM) and Partial Least Squares (PLS) approach to generate discriminant validity. The population in this study were teachers who were estimated. Questionnaires were used as part of the data collection method. The findings of the study showed a significant relationship between altruism, civic participation, politeness, self-efficacy, hope, and resilience with psychological well-being in early childhood teachers. The variables conscientiousness and optimism did not show a statistically significant positive effect. The results of this study provide a significant contribution to our understanding of the factors that influence the psychological well-being of early childhood teachers. In addition, the current findings of this study have important implications for the development of interventions and strategies aimed at improving the well-being of early childhood teachers. In conclusion, this study highlights the importance of specific dimensions of OCB and Psychological Capital in improving the psychological well-being of early childhood teachers. By focusing on the development of positive behaviors and psychological resources, educational stakeholders can create supportive environments that improve overall teacher well-being in early childhood education settings.